Strategi Komunikasi Pemasaran Digital pada Pariwisata Sumatera Barat Melalui Aplikasi Sumbar Hub - Purdi, Harefa; Amri Dunan (Jurnal Spektrum Komunikasi, 2023)
The development of technology, information, and communication is increasing the number of internet users continue to grow throughout the world every year, there is same in Indonesia. The West Sumatra Provincial Government utilizes the application as a means to provide information and serve the community more easily and reliably regarding tourism in the Province of West Sumatra by using the Sumbar Hub Application. The purpose of this study is to determine the Digital Marketing Communication Strategy in West Sumatra Tourism through the Sumbar Hub Application. This study uses a qualitative approach and descriptive method. Data collection techniques from interviews, observations, and documentation. The results of the study stated that the marketing carried out was in accordance with the desired functions and duties of the government, but was not yet well known to the public due to its limitations. This tourism digital marketing refers to geographical segmentation, the brand image of Sumatra Hub application is easy to use and reliable because of the characteristics of the appearance of the application and appropriate content ranging from photos to captions contained tourism information which is managed directly by the government of West Sumatera. Keywords: Marketing Communication Strategy, Digital Marketing, Tourism.